PENGEMBANGAN MEDIA PEMBELAJARAN CANVA PADA MATERI PERMINTAAN DAN PENAWARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Jelita Maria Christine Samosir; Khairuddin Ependi Tambunan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to develop a Canva-based learning medium on the demand and supply topic to improve the learning outcomes of tenth-grade students at SMAN 10 Medan and to examine its validity, practicality, and effectiveness. This research and development study used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The sample consisted of two classes selected through purposive sampling, an experimental class taught using the Canva-based medium and a control class taught using the printed textbook. Data were collected through validation questionnaires, student and teacher response questionnaires, and a multiple-choice achievement test administered as a pretest and posttest. The results showed that the medium was rated valid by media experts (84%), material experts (93%), and instructional design experts (90%). The practicality questionnaires showed very practical results from teachers (94%) and students (89%). Prerequisite tests indicated normally distributed and homogeneous data, and the t-test showed a significant difference between the two classes (sig. 0.000 < 0.05). The N-Gain score of the experimental class (0.63) was higher than that of the control class (0.43). It is concluded that the developed Canva-based learning medium is valid, practical, and effective in improving students' learning outcomes on the demand and supply topic.